Effect of different feeding methods and gut microbiota on premature infants and clinical outcomes - Liu, Manman; Chen, Cheng; Kang, Songhao; Kwon, Jung-il; Jin, Juan; Che, Huilian (Frontiers in Nutrition, 2022)
Premature infants require special care, and clinical feeding methods for this patient group are generally divided into breastfeeding and formula milk. This retrospective study investigated the effects of these two feeding methods on premature infants admitted to the neonatal intensive care unit between 2017 and 2020. Data regarding duration of complete enteral feeding, weight gain, and postnatal infections were collected, categorized, and compared. Pearson’s correlation coefficient was used to determine the correlation between the intestinal flora and clinical outcomes. Results revealed no differences between the two feeding methods, and neither had significant effects on clinical indicators in premature infants, although the gut microbiota may be an important factor influencing many clinical indicators. Results of this study suggest an important role for the gut microbiota in the care of premature infants and provide a basis for promoting the healthy development of this patient population.